Application of the “immunization islands” model to improve quality, efficiency and safety of a COVID-19 mass vaccination site - Signorelli, C.; Odone, A.; Gianfredi, V.; Capraro, M.; Kacerik, E.; Chiecca, G.; Scardoni, A.; Minerva, M.; Mantecca, R.; Musarò, P.; Brazzoli, P.; Basteri, P.; et al. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
After SARS-CoV-2 vaccines development came at an unprecedented speed, ensuring safe and efficient mass immunization, vaccine delivery became the major public health mandate. Although mass-vaccination sites have been identified as essential to curb COVID-19, their organization and functioning is challenging. In this paper we present the planning, implementation and evaluation of a massive vaccination center in Lombardy - the largest Region in Italy and the most heavily hit by the pandemic. The massive hub of Novegro (Milan), managed by the Gruppo Ospedaliero San Donato, opened in April 2021. The Novegro massimmunization model was developed building a layout based on the available scientific evidence, on comparative analysis with other existing models and on the experience of COVID-19 immunization delivery of Gruppo Ospedaliero San Donato. We propose a “vaccine islands” mass-immunization model, where 4 physicians and 2 nurses operate in each island, with up to 10 islands functioning at the same time, with the capacity of providing up to 6,000 vaccinations per day. During the first week of activity a total of 37,900 doses were administered (2,700/day), most of them with Pfizer vaccine (85.8%) and first doses (70.9%). The productivity was 10.5 vaccines/hour/vaccine station. Quality, efficiency and safety were boosted by ad-hoc personnel training, quality technical infrastructure and the presence of a shock room. Constant process monitoring allowed to identify and promptly tackle process pitfalls, including vaccine refusals (0.36%, below expectations) and post-vaccinations adverse reactions (0.4%). Our innovative “vaccine islands” mass-immunization model might be scaled-up or adapted to other settings. The Authors consider that sharing best practices in immunization delivery is fundamental to achieve population health during health emergencies.